Thoracolumbar Langerhans cell histiocytosis in a toddler - Zhi Gang Lan; Seidu A. Richard; Chuanfen Lei; Yan Ju (Elsevier, 2018)
Introduction: Langerhans cell histiocytosis (LCH) is a rare uni or multisystem disorder associated with extreme production of immunoreactive Langerhans cells. Although this disorder has been reported in all age groups, spinal involvement especially thoracolumbar spine is seldom reported in toddlers. Case presentation: We present a one (1) year, four (4) months female child with a history of recurrent fever, irritability and severe anemia of one (1) month duration. CT-scan and MRI revealed a collapsed twelfth thoracic vertebra (T12) body height greater than 95% with a huge intradural soft tissue mass. T12 cortectomy via posterior thoracolumbar approach was used to decompress the soft tissue part followed by interbody fusion with titanium cage filled with autologous iliac crest bone graft, fixation using plates and screws. Conclusion: We are of the view that surgical decompression of spinal LHC lesions with interbody fusion with titanium cage filled with autologous iliac crest bone graft and fixation using plates and screws is very crucial in relieving neurological deficits. However, the patient will need repeated surgeries as she advances with age in a timely manner to avert any neurological deficit that may occur. Keywords: Langerhans cell histiocytosis (LCH), Letterer-Siwe disease, Hand-Schüller-Christian disease, Eosinophilic granuloma